Effects of Different Monochromatic Light Combinations on Cecal Microbiota Composition and Cecal Tonsil T Lymphocyte Proliferation - Zhang, Yijia; Wang, Zixu; Dong, Yulan; Cao, Jing; Chen, Yaoxing (Frontiers in Immunology, 2022)
Emerging data demonstrated that the gut microbiota plays an important role in protecting the integrity of the epithelial barrier, forming a mucosal immune system, and maintaining intestinal homeostasis through its metabolites. However, the intestinal microbiota community can be affected by environmental factors, such as litter, photoperiod, or temperature. Thus, we investigated the effect of different monochromatic light combinations on cecal microbiota composition as well as explored the molecular mechanism by how the external light color information mediate cecal tonsil T lymphocyte proliferation. In this study, a total of 160 chicks were exposed to monochromatic light [red (R), green (G), blue (B), or white (W) light] or green and blue monochromatic light combination (G→B) from P0 to P42. The 16S rRNA microbial sequencing results showed that the richness and diversity of the cecum microbiota and the abundance of Faecalibacterium and Butyricicoccus were significantly increased in the G→B. With consistency in the upregulation of antioxidant enzyme ability and downregulation of pro-inflammation levels in the cecum, we observed an increase in the number of goblet cells, secretory IgA+ cells, tight junction protein (occludin, ZO-1, and claudin-1) and MUC-2 expression in the cecum of the G→B. The metabolomics analysis revealed that the relative abundance of metabolites related to butyrate was significantly increased in G→B. In an in vitro experiment, we found that butyrate could effectively induce T lymphocyte proliferation and cyclin D1 protein expression. However, these butyrate responses were abrogated by HDAC3 agonists, STAT3 antagonists, or mTOR antagonists but were mimicked by GPR43 agonists or HDAC3 antagonists. Thus, we suggested that G→B can indirectly affect the composition of cecal microbiota as well as increase the relative abundance of Faecalibacterium and Butyricicoccus and butyrate production by reducing the level of oxidative stress in the cecum. Exogenous butyrate could promote the T lymphocyte proliferation of cecal tonsil by activating the GPR43/HDAC3/p-STAT3/mTOR pathways.